Current use of antihypertensive drugs in Japanese patients with hypertension: Analysis by age group. Issue 6 (6th March 2018) - Ishida, Takayuki; Oh, Akinori; Hiroi, Shinzo; Shimasaki, Yukio; Tsuchihashi, Takuya
Abstract : Aim: To analyze the current use of antihypertensive drug classes in Japanese hypertensive patients stratified by age, highlighting differences between older and younger patients. Methods: A nationwide medical database was used to evaluate antihypertensive use in patients (aged ≥20 years) who had received a prescription for one or more antihypertensive drug as an outpatient from April 2014 to March 2015. Patients ( n  = 59 867) were age‐stratified into three groups: <65 years (28.7%), 65–74 years (33.1%) and ≥75 years (38.2%). Results: The mean number of antihypertensive drugs prescribed for patients in the overall population was 1.9 ± 1.0, with no appreciable differences between age groups. The most commonly prescribed drug classes for all ages were calcium channel blockers (CCB) and angiotensin II receptor blockers (ARB). CCB were prescribed more often than ARB in the 65–74 years (66.9% vs 60.5%) and ≥75 years (70.4% vs 56.8%) years age groups, and ARB were prescribed more often than CCB in patients aged <65 years (63.1% vs 61.9%). There were minimal differences by age in prescription rates for β‐blockers, angiotensin‐converting enzyme inhibitors and thiazide diuretics. ARB prescription rates were lower in patients aged ≥75 years with diabetes mellitus or renal disease than in younger age groups. Prescription rates for loop diuretics were higher in patients aged ≥75 years than in younger age groups, especially among those with renal disease. Conclusions: Antihypertensive drugs selected for patients aged ≥75 years differed from those selected for younger patients, in particular CCB and loop diuretics (prescribed more often), and ARB (prescribed less often).Geriatr Gerontol Int 2018; 18: 899–906 .